Extraocular sebaceous carcinoma accompanied by invasive squamous cell carcinoma: The first case report and consideration of histogenesis. Issue 4 (21st December 2017) - Kogame, Toshiaki; Ohe, Shuichi; Yamazaki, Fumikazu; Okamoto, Hiroyuki; Kiyohara, Takahiro
Abstract: A 61‐year‐old man presented with a dome‐shaped nodule, 1.2 cm in size, with a central crater covered by keratinous material near the left lateral malleolus. Histological findings demonstrated a basophilic circular cone in the center, surrounded and sharply demarcated by a broad eosinophilic area. The central conical mass was composed mainly of atypical basaloid cells intermingled with scattered atypical sebaceous cells with scalloped nuclei and microvesicular cytoplasms, suggesting sebaceous carcinoma. The peripheral area consisted of atypical keratinizing squamoid cells without sebaceous cells, suggesting invasive squamous cell carcinoma. Atypical sebaceous cells were positive for adipophilin. Atypical basaloid cells were positive for 34βE12 and CAM5.2. Peripheral squamoid cells were positive for 34βB4 and 34βE12 throughout, and were positive for LHP1 in the superficial layer. We herein describe the first case of extraocular sebaceous carcinoma accompanied by invasive squamous cell carcinoma, which might have arisen from biphasic differentiation of cancer stem cells.